Clinical efficacy analysis of Ahmed glaucoma valve implantation in neovascular glaucoma and influencing factors: A STROBE-compliant article. Issue 42 (October 2017) - He, Ye; Tian, Ying; Song, Weitao; Su, Ting; Jiang, Haibo; Xia, Xiaobo
Abstract : Abstract: This study aimed to evaluate the efficacy of Ahmed glaucoma valve (AGV) implantation in treating neovascular glaucoma (NVG) and to analyze the factors influencing the surgical success rate. This is a retrospective review of 40 eyes of 40 NVG patients who underwent AGV implantation at Xiangya Hospital of Central South University, China, between January 2014 and December 2016. Pre- and postoperative intraocular pressure (IOP), visual acuity, surgical success rate, medications, and complications were observed. Surgical success criteria were defined as IOP ⩽21 and >6 mm Hg with or without additional medications. Kaplan–Meier survival curves and Multivariate cox regression analysis were used to examine success rates and risk factors for surgical outcomes. The mean follow-up period was 8.88 ± 3.12 months (range: 3–17). IOP declined at each visit postoperatively and it was statistically significant ( P < .001). An average of 3.55 ± 0.86 drugs was applied preoperatively, while an average of 0.64 ± 0.90 drugs was used postoperatively, with the difference being of statistical significance ( P < .05). The complete surgical success rate of 3, 6, and 12 months after the operation was 85%, 75%, and 65%, respectively. Meanwhile, the qualified success rate of 3, 6, and 12 months after the operation was 85%, 80%, and 77.5%, respectively. The multivariate cox regression analysis showed that age (hazard ratio: 3.717, 7.246; 95% confidence interval: 1.149–12.048, 1.349–38.461; P = .028, .021) was influencing factors for complete success rate and qualified success rate among all NVG patients. Gender, previous operation history, primary disease, and preoperative IOP were found to be not significant. AGV implantation is an effective and safe surgical method to treat NVG. Age is an important factor influencing the surgical success rate.